A way to incorporation of thermodynamics into quantum theory - Golubjeva, O.N.; Sukhanov, A.D. (Вопросы атомной науки и техники, 2012)
We suggest an approach allowing restrict a gap between macro- and micro descriptions of nature (i.e. between statistical thermodynamics and quantum mechanics) on the basis of a new heat bath model in the form of cold and heat vacua. Despite of standard quantum mechanics we start from microtheory in the form of ħ,k-dynamics suggested by us earlier. Its concept, in general case, founds on use of complex wave function which amplitude and phase are depended on temperature.